Access to support services for individuals who experience intimate partner violence during stressful life events (SLEs) in high-income countries: Protocol for a scoping review. - Dina Idriss-Wheeler; Ziad El-Khatib; Sanni Yaya (PLoS ONE)
Background Women, gender minorities and their children are at heightened risk of intimate partner violence (IPV) following stressful life events (SLE). The increase in IPV during the global pandemic of the Novel Coronavirus (COVID-19) is recent evidence. Studies have linked IPV to poor health, resulting in lower mental, physical, sexual, and reproductive health outcomes. IPV has also been shown as a barrier to labour force participation, leading to negative socioeconomic outcomes (i.e., low or no employment). Formal and informal supports help individuals who experience IPV, but it is unclear if and how these are being accessed during SLEs such as environmental disasters, pandemics, and economic recessions. Accessibility to programs is an issue in normal times because of stigma, social norms, and lack of knowledge; this has been further amplified by situations where individuals who experience violence are isolated physically and emotionally, as well as face controlling behaviours by their perpetrators of violence. This scoping review will be used to conduct a comprehensive review of literature and address the research question: What is known in published literature about access to services by individuals who experience IPV during stressful life events in high-income countries? Methods The following electronic databases will be searched for relevant publications: MEDILINE (OVID), Embase (OVID), PsychINfo (OVID), CINAHL (EBSCO), Global Health (EBSCO), Gender Watch (ProQuest), Web of Science and Applied Social Sciences Index & Abstracts (ProQuest). Key terms and medical subject headings (MeSH) will be based on previous literature and consult with an expert librarian. The major concepts include 'stressful life events' AND intimate partner violence' AND 'access to services'. Google, Google Scholar, and the WHO website will be used to search for grey literature, books/chapters, and programme reports as well as references of relevant reviews. Studies will be screened and extracted by two reviewers and conflicts resolved through discussion or a third reviewer. Both quantitative and qualitative analysis of relevant data will outline key findings. Discussion The scoping review will provide synthesized and summarized findings on literature regarding access to informal and formal social supports by victims of IPV during SLEs (i.e., pandemics and natural/environmental disasters/emergencies, economic recessions) where possible, highlighting key barriers, facilitators and lessons learned. Findings have potential to inform programs, policies, and interventions on accessibility to necessary support and health services during disasters.